PENGARUH PERTUMBUHAN PERUSAHAAN, PELUANG INVESTASI, ARUS KAS, DAN PERJANJIAN UTANG TERHADAP KONSERVATISME AKUNTANSI (PERUSAHAAN SEKTOR KESEHATAN PERIODE 2021-2023) - Hidayatul Fadilah Giawa; Muhammad Ahyaruddin; Dwi Fionasari (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to examine the effect of company growth, investment opportunities, cash flow, and debt covenants on accounting conservatism in healthcare companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The study employed a quantitative approach with secondary data in the form of annual financial reports obtained from the official IDX website. The sample was determined through purposive sampling and consisted of 24 companies with a total of 72 observations over three years. The dependent variable was accounting conservatism, measured using the accrual basis, while the independent variables included company growth, investment opportunities, cash flow, and debt covenants. Data analysis was performed using multiple linear regression with SPSS version 22 software, accompanied by classical assumption tests to ensure model validity. This study is expected to provide theoretical contributions to the development of accounting studies, particularly regarding the factors influencing accounting conservatism. Practically, the research results are expected to serve as a reference for company management in applying the principle of conservatism to improve the quality of financial reports and maintain stakeholder trust. These findings can also provide input for investors and creditors in evaluating the financial performance of companies in the healthcare sector.